Estimation of Magnitude of Heterosis and Heritability in Sunflower in 8X8 Half Diallel Population - Rashid, M. H.; Islam, A. K. M. Aminul; Rasul, M. G.; Saikat, M. M. H.; Ahmed, J. U. (Journal of Agricultural Studies, 2021)
Selected eight inbreed line were used in crossing as half diallel fashion to find out different genetic parameter as well as targeting superior combination for hybrid vigour. Sunflower first introduce in Bangladesh 1980 by Bangladesh Agricultural Research Institute and Mennonite Central Committee. BARI Sunflower-1(Kironi) and BARI Sunflower-2 is only two released variety. But major obstacles for sunflower cultivation are both varieties are more than 1.50m height and require > 100 days for maturity. As this country is facing climate change unfavorable weather, sunflower cannot withstand in stormy weather. Specially at the time of prematurity stormy weather causes lodging due to over height, it is essential to develop dwarf stature plant. Due to strong crop competition in winter it cannot fit in major cropping pattern T-Aman-Mustard-Boro due to it long duration. Bangladesh has accessible land of 0.85 million hectares in saline areas (Banik et al., 2011). These lands can be used for sunflower cultivation as it is moderately saline tolerant (Rahman et. al. 2018). On the other hand in different part of Bangladesh (e.g. Cumilla, Manikgonj, Sherpur, Jamalpur, Netrokina, Tangail, Dinajpur, etc.), a huge amount of lands are kept fellow after T. Aman harvest. These current fellow lands can be easily used by sunflower cultivation if short duration varieties are available. Both plant height and days to maturity were considered as favorable for negative heterosis to obtain dwarf plant stature and short duration plant to fit in existing cropping pattern in Bangladesh. Positive heterosis is considered desirable for other yield contributing traits. The hybrid HE15, HE17 and HE16 showed significant negative heterosis both for mid parent and better parent. Negative heterosis for plant height is desirable to adopt hybrid in unfavorable weather condition. The Hybrid HE15 showed both for significant negative mid parent and better parent heterosis. High heritability along with significant mid parent and better parent heterosis indicate scope of utilization of hybrid as commercial and further use in breeding programmes. Several outstanding cross combinations, HE17, HE16, HE14, HE15, and HE18 showed significant and desirable heterosis for seed yield per plant over mid parent and better parent. The hybrid combinations HE17, HE16 and HE14 could be utilized to exploit the heterosis as well as commercial multiplication of seed to get direct benefit by the farmers.